How’s your waiting list? - Gulino, Virginia; Ricci, Beatrice; Russo, Stanislav; Nigro, Marco; Gallerani, Edoardo; Lombardo, Elena; Perger, Peter; Campagna, Anselmo; Buccioli, Matteo (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Surgical waiting lists pose a major challenge for public healthcare systems, affecting access to care and the perceived quality of services. However, there is no standardized method for assessing the efficiency and management of waiting lists. Study Design. This study proposes a model based on Key Performance Indicators (KPIs) to measure the Waiting List sustainability of surgical waiting lists, evaluating their balance, attractiveness, efficiency, and timeliness. Methods. Three main KPIs were defined and applied to both hypothetical and real datasets, analyzing data collected at the IRCCS Istituto Ortopedico Rizzoli from January 2024 to September 2024. Statistical analysis was conducted using Excel, calculating ratios between enrolled, admitted, canceled, and overdue patients on the waiting list. Results. The analysis showed that some hospital departments have a balanced management of waiting lists, while others exhibit critical issues, with high rates of overdue or canceled patients. The graphical representation of the indicators helped identify areas for improvement in resource management. Conclusions. The adoption of standardized KPIs could serve as a valuable tool for monitoring and optimizing waiting lists, supporting strategic decisions to enhance access to healthcare services.